Educação permanente em saúde como estratégia para redução da mortalidade materna - Silva, Juliete Teresinha (2017)
Maternal mortality is still a problem of public health in all the world, mainly when we take a look at the developing countries. The reason for maternal mortality (RMM) enables the visualization of the place that women occupy in a society and how the health system takes care of their specific need based on the principle of equity. During the pre-natal a careful attention can identity pregnant women that have a bigger risk making it possible that we make a planned approach that will avoid occurrences of emergency situations that are always accompanied by bigger chances of maternal and neonatal morbimortality. Evaluate the perception of the professionals in the health field, their practice in the care of pregnancy in the primary assistance for the elaboration of a proposal of a permanent education program in health, as a strategy to reduce the maternal mortality in the county of Jataí in the state of Goiás. It was done a descriptive, exploratory, transversal study, of a qualitative approach in the health education. The secondary data referring maternal mortality in Brazil in these five years (2011 to 2015) were extracted from information of the ministry of health (SIM – System of Information of Mortality). The collecting of data referring the perception of professionals about permanent health education was obtained through a focal group. The analysis of the data was done through content analysis. The RMM in the county of Jataí in the year of 2015 was 142 deaths/100,000 born alive, similar to the year of 1990 when it was established as a goal of the 5th ODM that this indicator reached the level of 35 deaths / 100,000 born alive in 2015. The pre natal is done by a multiprofessional team that knows their role in the care of pregnancy in APS, however fragile points were pointed concerning the quality of this assistance, the team work and the knowledge and practice of EPS. The professionals involved in the research do not know the PNEPS, and there is not a practice of EPS in the work place considering that the knowledge of the health education limits itself to the education destined to SUS users. Acting at APS by the practice of a permanent education in health is the proposal strategy to contribute for the changing of the scenary of maternal mortality in the place of the studies.